EXTRACTION AND CHARACTERIZATION OF ANTIBACTERIAL PIGMENT FROM ROSEOMONAS GILARDII YP1 STRAIN IN YERCAUD SOIL - N, SIDDHARTHAN; R, SANDHIYA; N, HEMALATHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The current study is focused on antibacterial pigment production from Yercaud hills region soil bacteria. Methods: In this present study, a soil sample was collected from a coffee plantation in Yercaud, Salem district. The collected soil sample was used to isolate the pigment-producing bacterial strains. The pigments were extracted by acidified ethanol and there used to screen the antibacterial activity against clinical pathogens. The potential antibacterial pigment producer was identifying and the pigment was characterized by ultraviolet spectroscopy, thin-layer chromatography, and Fourier transform infrared (FT-IR) and also evaluate the minimum inhibitory concentration of pigment against clinical pathogens. Results: The pigment-producing bacterial strains were isolated from Yercaud soil, among the isolates, YP1 was maximum activity against test pathogens. The potential pigment producer was identified as Roseomonas gilardii. The extracted pigments showed the maximum absorbance at 450 nm and their functional groups were identified using FT-IR analysis. Conclusion: Based on the results, the pigment was extracted from R. gilardii and it may serve as potential antibacterial pigment of interest in the food industries, textile industries in natural colorant, and cosmetic industries.